Analysis of the Anthropogenic and Biogenic NOx Emissions Over 2008–2017: Assessment of the Trends in the 30 Most Populated Urban Areas in Europe. Issue 11 (31st May 2021) - Fortems‐Cheiney, A.; Broquet, G.; Pison, I.; Saunois, M.; Potier, E.; Berchet, A.; Dufour, G.; Siour, G.; Denier van der Gon, H.; Dellaert, S. N. C.; Boersma, K. F.
Abstract: We use the OMI‐QA4ECV‐v1.1 NO2 tropospheric columns over the 10‐year 2008–2017 period to confront satellite‐based trends in NO2 concentrations to those from the state‐of‐the‐art regional chemistry‐transport model CHIMERE and to evaluate the bottom‐up anthropogenic and biogenic NOx emissions in Europe. A focus is made for the 30 most populated urban areas in Europe. Over urban areas in Western Europe, except for coastal cities, OMI confirms the drop in the simulated CHIMERE NO2 tropospheric columns based on the latest country emission official reporting. OMI hardly shows significant negative trends over Central and Eastern Europe urban areas. Increasing biogenic emissions helps reconciling CHIMERE and OMI trends over urban areas in Central Europe and over rural areas, confirming the importance of accounting for non‐anthropogenic emissions to assess long‐term trends. Over Eastern Europe, our results question emission reductions estimated for particular sectors and in particular the road transport, public power, and industrial emissions. Plain Language Summary: We evaluate anthropogenic and biogenic nitrogen oxides (NOx ) emissions in Europe by analyzing nitrogen dioxide (NO2 ) 10‐yr trends both from satellite observations and from simulations. A focus is made for the 30 most populated urban areas in Europe, particularly exposed to air pollution. The similarities and discrepancies between simulations and satellite observations indeed must be investigated. It is important particularly for policy implications as anthropogenic emissions are based on the official reported emissions form the basis for negotiation on emission reductions in the EU and are used to assess if countries meet their agreed emission ceilings. Key Points: Over urban areas in Western Europe, OMI confirms the drop of the simulated CHIMERE NO2 tropospheric vertical column density columns, based on the latest country emission reporting Increasing biogenic emissions reconciles CHIMERE and OMI over urban areas in Central Europe and over rural areas, confirming their importance to assess long‐term trends Over Eastern Europe, our results question emission reductions estimated for particular sectors such as road transport, public power and industrial emissions